KLASIFIKASI KUALITAS TANAH MENGGUNAKAN METODE GRADIENT BOOSTING (STUDI KASUS: BUDIDAYA KACANG TANAH) - Diah Kamalia; Meidya Koeshardianto; Wahyudi Setiawan (Jurnal Multidisipliner Kapalamada, 2026)
This study aims to determine soil quality in peanut cultivation to support precise decision-making for farmers. Peanuts were selected due to their economic and nutritional importance in Madura, as well as their strong dependence on soil conditions. The research method used is the Gradient Boosting Classifier, utilizing four parameters: soil pH, soil moisture, air temperature, and air humidity. This method builds models iteratively by reducing errors from previous models by following the gradient movement towards the negative. The collected data are then processed through a classification approach to accurately determine soil suitability for peanut cultivation. The results indicate that the method can identify relationships among soil variables, making it a useful tool for predicting soil suitability for cultivation. The system is developed to enhance decision-making by enabling real-time soil condition monitoring with precision, improving soil management effectiveness, and optimizing sustainable and efficient cultivation practices for farmers in Buluh, Socah, Bangkalan.